Is there a relationship between patient age, tumor multifocality, and capsular invasion in papillary thyroid carcinoma? Retrospective evaluation of pathology specimens - Taşkın, Halit Eren; Karatas, Adem (Journal of Surgery and Medicine, 2022)
Background/Aim: Papillary thyroid carcinoma (PTC) is the most prevalent of thyroid gland cancers. Although PTC generally is successfully treated, risk factors such as age, tumor size, thyroid capsule invasion, multifocality, and presence of metastases can negatively affect the prognosis. We aimed to assess the relationship between multifocality, capsular invasion, and patient age (≤45 vs >45 years of age) in PTC, along with other relevant tumor characteristics. Methods: In this retrospective cohort study, evaluation of pathology findings in patients with a PTC diagnosis or thyroid nodules suspicious for PTC, the frequency of multiple specimen related prognostic factors by age was compared. Only patients initially operated with papillary thyroid cancer suspicion or definite diagnosis without distant organ metastasis were included. All the other patients with recurrent disease were excluded. Results: Between 2008 and 2014, 466 patients with PTC tumors were operated. Tumors were multifocal in 62 (13.3%) patients and unifocal in 404 (86.7%). When multifocality was compared in two patient groups (≤45 years vs. >45), it was slightly higher in patients >45 years old (14.4%) vs ≤45 (11.5%; p=0.374). The multifocality rate in patients with a tumor size of >1 to ≤2 cm was significantly higher (17.5%) than in all other tumor size groupings (0.0-13.7%; p=0.002). Thyroid capsule invasion occurred in 39.1% of patients in the younger group vs 33.6% in the older group (p=0.05). Conclusion: In light of our study’s findings, including confirmation by multivariate analysis, age, as represented by the >45 year cutoff value, should not be considered an independent prognostic risk factor in planning treatment of PTC. The individual patient, tumor characteristics, and local and distant metastases status should remain the most important criteria for treatment selection and follow-up care in all patient age groups.